The Influence of Work Motivation and Job Training on Employee Performance at PT Pertama Logistic Service, Subang Branch - Lidya Pricilla; Irma Sari Octaviani (Jurnal Ekonomi, Akuntasi dan manajemen Indonesia (JEAMI), 2026)
Employee performance is a critical factor influencing organizational effectiveness, particularly in the logistics industry, where operational efficiency and service quality determine business competitiveness. This study aims to examine the effects of Work Motivation and Job Training on Employee Performance at PT Pertama Logistic Service, Subang Branch, Indonesia. A quantitative research approach with an explanatory design was employed. Data were collected through structured questionnaires distributed to 80 employees using a saturated sampling technique. The collected data were analyzed using multiple linear regression with IBM SPSS Statistics version 26. The findings indicate that Work Motivation has a positive and significant effect on Employee Performance (β = 0.390, t = 3.716, p < 0.001). Similarly, Job Training positively and significantly influences Employee Performance (β = 0.342, t = 3.258, p = 0.002). Furthermore, the simultaneous regression analysis demonstrates that both variables significantly affect Employee Performance (F = 27.701, p < 0.001), explaining 41.8% of the variance in employee performance. These findings suggest that strengthening employee motivation and implementing continuous, needs-based training programs can improve employee competencies, productivity, and overall organizational performance. The study contributes to the human resource management literature by providing empirical evidence from the Indonesian logistics sector and offers practical implications for organizations seeking to enhance workforce performance.